Learning styles of Fully Residential Schools’ Students in Mathematics through the Flipped Classroom Method: Do Gender Factors Cause Different Impacts? - A. Rahman, Azlina; Zaid, Norasykin Mohd; Aris, Baharuddin; Mohamed, Hasnah; Abdullah, Zaleha (EDUCATUM Journal of Science, Mathematics and Technology, 2017)
This study was conducted with its aim to measure the dominant learning styles of Fully Residential Schools’ students. The need to acquire the dominant learning styles of these students arose since they are bound to the school environment which limits learning styles according to their inclination. Hence, individual and group learning styles were developed to fulfil the needs of the students in context of their favourite learning styles. However, there were raised concerns whether learning styles would cause different impacts, based on gender if they are integrated in Mathematics. This study gave the answer through a survey conducted on a total of 61 Fully Residential Schools’ students, 31 of whom underwent the proposed intervention in the form of flipped classroom method, while the remaining 30 were in the control group. The findings of the study obtained by a descriptive analysis showed that group learning was the dominant learning style adopted by the students. In addition, the findings also showed that, there was no significant difference in learning styles based on gender. It was concluded that Fully Residential Schools’ students needed group activities in their learning and their learning styles were not focused only on one particular type. Regardless of gender, they were capable of being actively involved in group activities. So this study had the potential to be implemented in the 21st century learning which emphasizes on group activities that should integrate learning styles well in tandem with the teachers’ teaching.